Pengaruh Penggunaan Model STAD Terhadap Hasil Belajar Siswa Dalam Pembelajaran PKn Di kelas V Sekolah Dasar - lestari, widiya; hamimah, hamimah; Yunisrul, Yunisrul (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This research is done done due to the fact that 5th  grade student’s learning outcomes of civics subject were still low. Moreover, the teacher had never applied the STAD model in the classroom. This research aims at finding out yhe effects of applying the model toward the students’ learning outcomes. This quasi experiment used the nonequivalent control group design. The population was all 5th grade students of primary schools. Samples were chosen by using the saturation sampling techique in which VB acted as the experimental class and VA as the control one. The research result shows that bby using t-test with the level of significant of 0,05, tcount > P-Value and tcount = -3.421 and P-Value = 0.001. Thus, the H1 hypothes is accepted.Keyword : the STAD Model, Learning Outcomes